A EVALUASI KONDISI GEDUNG GEREJA DI JAKARTA BARAT DENGAN METODE CONDITION SURVEY PROTOCOL (CSP) 1 - Christohodos Marlissa; Hans Dermawan; Widsri Palamba (LPPM Universitas Negeri Jakarta, 2025)
The number of churches in West Jakarta shows an increase. Despite the growth in quantity, the decline in the quality of church buildings is a concern. This decline is mainly caused by aging structures, climate conditions, and lack of maintenance and preservation. The collapse of the ceiling is one of the impacts. This research applies the CSP 1 matrix, a visual assessment method, to examine the condition of church building components systematically. CSP 1 matrix enables researchers to evaluate defects, prioritize repairs, and assess the overall rating of church buildings. Research indicated that 63% of churches are in good condition, while 37% are in fair condition and none classified as dilapidated. Issues identified include discoloration and peeling of paint on architectural components, structural cracks ranging from 0.2 to 1 millimeter, and loose electrical sockets. These defect results are due to weather, material quality, building age, and inadequate maintenance planning, compounded by financial constraints in churches with smaller congregations. Matrix value variations reveal different levels of maintenance for each church building. Higher matrix values require better planning and prioritized repairs to maintain quality and ensure functionality and safety.